IMPLEMENTASI METODE GALLERY WALK TERHADAP MINAT DAN KEMAMPUAN KOGNITIF SISWA PADA MATERI VIRUS - Lesy Luzyawati; Idah Hamidah (Universitas Majalengka, 2020)
The low student learning outcomes and interest in learning biology are caused by several factors, one of which is the lack of use of learning methods that can make students active. One way to overcome these problems is through the use of gallery walk learning methods. The purpose of this study was to determine the effect of the gallery walk method on viral material on cognitive abilities and learning interests of students at SMA Negeri 1 Losarang Indramayu. This study uses True Experimental Design with Posttest-Only Control Design. The results of data analysis showed that the gallery walk learning method affected the cognitive abilities of students on virus material. Analysis of student learning interest data on virus material is in the very high category